2021
DOI: 10.24036/jea.v3i2.363
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Pengungkapan Emisi Karbon dan Annual Report Readability terhadap Nilai Perusahaan

Abstract: The objevtive of this study is to investigate the influence of carbon emissions disclosure and annual report readability on firm value. The sampel consist of firms that listed in PROPER’s and Indonesian Stock Exchange (BEI) for the year (2016-2018). By using multiple regression analysis, the results show that carbon emissions disclosure has a positive influence on firm value, while it has no significant influence with annual report readability. This study contributes to the accounting field in maximizing the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 4 publications
(11 reference statements)
1
6
1
4
Order By: Relevance
“…(Sari and Budiasih, 2021) in their research revealed that carbon emission disclosures have a positive effect on firm value. The result in this study, support research conducted by (Alfayerds and Setiawan, 2021) which shows that the carbon emissions disclosure has a positive effect and significant on firm value. With the company making disclosures, one of which is: Carbon Emission Disclosure then the company will get a good name and attention from the community and the other stakeholders.…”
Section: The Relationship Of Carbon Emission Disclosure and Firm Valuesupporting
confidence: 89%
See 3 more Smart Citations
“…(Sari and Budiasih, 2021) in their research revealed that carbon emission disclosures have a positive effect on firm value. The result in this study, support research conducted by (Alfayerds and Setiawan, 2021) which shows that the carbon emissions disclosure has a positive effect and significant on firm value. With the company making disclosures, one of which is: Carbon Emission Disclosure then the company will get a good name and attention from the community and the other stakeholders.…”
Section: The Relationship Of Carbon Emission Disclosure and Firm Valuesupporting
confidence: 89%
“…The results of this study contradict the theory of legitimacy, which explains that companies will tend to seek legitimacy from the surrounding environment related to the company's operating activities, one of which is by providing information related to the company's operating activities that have an impact on the environment. Companies that have gained legitimacy should tend to improve their image and reputation in the eyes of the public, which will have an impact on the overall value of the company (Alfayerds and Setiawan, 2021), but the opposite is found from the results of this study which says that not all companies that get legitimacy will improve the company's image in society. This study also contradicts the research conducted by Sari and (Budiasih, 2021) (Alfayerds and Setiawan, 2021) and shows that carbon emissions' disclosures have a positive effect on firm value.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…The implementation of CSR is believed to improve company performance, investors tend to invest in companies that carry out CSR activities (Astuti & Nugrahanti, 2015) With this phenomenon, issues regarding the environment and the sector's responsibility to the environment have become a more concern for the public and investors, this can also affect the sustainability of the sector in the future. Companies that are more comprehensive and broader in reflecting their carbon emissions can increase their value in the eyes of investors or potential investors by attracting the attention of investors and potential investors (Alfayerds & Setiawan, 2021). The market reaction to the announcement/disclosure can be seen from changes in stock prices and stock trading volume activities (Nurdin andFani, 2006 in Falichin, 2010).…”
Section: Introductionmentioning
confidence: 99%